Office as Implementing Complete Systematic Land Registration Acceleration in order to realize - Fitri Hariadi; Priambodo Adi Wibowo; Ebit Rudianto (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
The purpose of this study is to determine the role of the land office in the acceleration implementation programcomplete systematic land registration (PTSL). The research method used is a normative juridical research method, which focuses on the study starting from the provisions of the applicable laws and regulations, accompanied by legal theories and principles related to the problems studied. The results of the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning Complete Systematic Land Registration Article 1 number 2 regarding the meaning of PTSL, namely Land Registration activities for the first time which are carried out simultaneously for all Land Registration objects throughout the territory of the Republic of Indonesia. Indonesia in one village/kelurahan or other name equivalent to that, which includes the collection of physical data and juridical data regarding one or several objects of Land Registration for the purposes of its registration. Regulation of the Minister of ATR/Head of BPN Number 6 of 2018 Article 2 point 2 states that PTSL aims to provide legal certainty and legal protection of community land rights based on simple, fast, smooth, safe, fair, equitable and open and accountable principles, so as to improve the welfare and prosperity of the community and the state economy, as well as reducing and preventing land disputes and conflicts. The Sidoarjo Regency Land Office as the executor of PTSL acceleration for the Sidoarjo Regency has made efforts to increase public interest in registering their land, given the complex stages of land registration implementation, and various obstacles in its implementation, but this does not become a barrier for the Sidoarjo Regency Land Office in achieving the target, which can be seen from the achievement of the targets that have been achieved.